Alterations of melatonin receptors MT1 and MT2 in the hypothalamic suprachiasmatic nucleus during depression - Wu, Ying-Hui; Ursinus, Jeanine; Zhou, Jiang-Ning; Scheer, Frank A.J.L.; Ai-Min, Bao; Jockers, Ralf; van Heerikhuize, Joop; Swaab, Dick F. (Journal of affective disorders, 2013)
The pineal hormone melatonin regulates circadian rhythms, largely by feedback on the central biological clock of the brain, the hypothalamic suprachiasmatic nucleus (SCN). This feedback is mediated by the melatonin receptors, melatonin receptor 1 (MT1) and melatonin receptor 2 (MT2). The circadian system may play a role in the pathophysiology of mood disorders, and indeed, melatonin-receptor agonists are considered a potential therapy for depression. In order to investigate melatonin receptors in the SCN during depression, and their relationship to the major neuropeptides in the SCN, vasopressin (AVP) and vasoactive intestinal peptide (VIP), we studied the SCN in 14 depressed patients (five major depression and nine bipolar disorder) and 14 matched controls by immunocytochemistry. We show here that hypothalamic MT2 receptor immunoreactivity was limited to SCN, the supraoptic nucleus and paraventricular nucleus. We found that numbers of MT1-immunoreactive (MT1-ir) cells and AVP and/or VIP-ir cells were increased in the central SCN in depression, but numbers of MT2-ir cells were not altered. Moreover, the number of MT1-ir cells, but not MT2-ir cells was negatively correlated with age at onset of depression, while positively correlated with disease duration. Although every post-mortem study has limitations, MT1 receptors appeared specifically increased in the SCN of depressed patients, and may increase during the course of the disease. These changes may be involved in the circadian disorders and contribute to the efficacy of MT agonists or melatonin in depression. Moreover, we suggest that melatonin receptor agonists for depression should be targeted towards the MT1 receptor selectively.